Haemodialysis and haemofiltration on cardiopulmonary bypass. - Hakim, M (1985)
Over a three year period we have used haemodialysis and haemofiltration in parallel with cardiopulmonary bypass in 26 patients. Impaired renal function and excessive fluid retention have been the main indications. Patients on haemodialysis programmes for end stage renal failure did not require further dialysis until at least the third postoperative day, when they could tolerate the haemodynamic disturbance of dialysis. In the other patients these techniques proved valuable in reversing the effects of haemodilution and in controlling the concentration of serum potassium. Our experience has confirmed that haemodialysis and haemofiltration in parallel with cardiopulmonary bypass are useful adjuncts in the perioperative management of patients with impaired renal function undergoing open heart surgery. The techniques are also effective in correcting the fluid retention and biochemical imbalance in patients with congestive cardiac failure, including those with heart transplants.